COMMUNICATION SECURITY IN THE MQTT PROTOCOL FOR MONITORING INTERNET OF THINGS DEVICES USING METHODS ELLIPTIC CURVE CRYPTOGRAPHY - Axel Natanael Salim; Tata Sutabri; Edi Surya Negara; M Izman Herdiansyah (Jurnal Teknik Informatika (Jutif), 2024)
The emergence of the IoT has become one of the most significant technology trends. The application of IoT is aimed at enhancing efficiency, comfort, and facilitating various human activities. One key aspect of IoT implementation is efficient communication between devices, with one of the most commonly used protocols being MQTT protocol. MQTT enables the transmission of data in real-time or based on specific events, although there are still several challenges that need to be addressed. One of the main challenges of MQTT is information security issues, prompting this research to examine effective solutions to enhance communication security in IoT applications that utilize MQTT protocol. One method of securing communication between IoT devices can involve using lightweight cryptographic communication security methods such as ECC method. ECC method is chosen because it utilizes shorter keys while still providing high security, making it more efficient when implemented on IoT devices. The results obtained indicate that data sent to MQTT Broker cannot be read and converted manually, ensuring much safer data transmission. Based on the test results, the tool can effectively read, process, and send data to MQTT Broker. QoS measurements on the system revealed that data encrypted and sent from the subscriber to MQTT Broker had an average delay time of 54.1 ms, throughput of 410.4 bps, zero packet loss, and jitter of 0.00 ms. Looking at the research findings, it can be concluded that this ECC method could serve as a solution to data communication security issues in the MQTT protocol.